Vascular endothelial growth factor enhances venous thrombus recanalisation and organisation - Waltham, Matthew; Burnand, Kevin G.; Collins, Michael; McGuinness, Catharine L.; Singh, Inderjit; Smith, Alberto (Thrombosis and Haemostasis, 2003)
Vascular endothelial growth factor (VEGF) is a regulator of physiological and pathological angiogenesis and is found in naturally resolving experimental venous thrombi, where it may also regulate recanalisation. In this study VEGF protein was injected into venous thrombi to determine if this enhanced recanalisation and organisation. A rat model of inferior vena cava (IVC) thrombosis was used. Thrombi were formed in 3 groups (n = 3 per group). 10 μl 125I-VEGF was directly injected into thrombus thirty minutes after induction. Three hours, 1 day and 6 days later thrombus, IVC, and other tissues were harvested. 125I-VEGF was mostly distributed in the thrombus and the IVC, with smaller amounts in other tissues. Thrombi were formed in a further 4 groups (n = 6 per group).Thirty minutes after induction control solution or 1 ng, 10 ng or 100 ng recombinant human VEGF165 was injected directly into the thrombus. Lumen recanalisation, thrombus organisation and monocyte content were measured on digitised sections by image analysis. In animals treated with 10 ng of VEGF there was a greater area of lumen recanalisation [mean 5492 pixels, standard error of mean (sem) 922] compared to controls (mean 2974, sem 385) (P = 0.005). There was a significant increase in the organisation score in all treated animals (1 ng: mean 70, sem 1.7, P = 0.0025; 10 ng: mean 70, sem 2.0, P = 0.0042; 100 ng: mean 72, sem 1.9, P = 0.0003) compared to controls (mean 63, sem 1.7). The monocyte content was lower in the animals treated with 1 ng VEGF (mean 3.8% of thrombus area, sem 0.3%) compared to controls (mean 5.5%, sem 0.4%) (P = 0.0008).The proportion of monocytes migrating to the centre of the thrombus increased in a dose-related manner. VEGF may prove to be of use in the treatment of venous thrombosis.
Keywords: Thrombus resolution; angiogenesis; VEGF; recanalisation